ACTIVITIES OF ORTHODOX MONASTERIES IN THE TERRITORY OF WESTERN UKRAINE (1992–2018 РР.) (Південний архів (історичні науки), 2022)
Goal. The article examines the formation of Orthodox monasteries and the institute of monasticism in the UOC-KP during the period of Ukraine’s independence. 1988 was a significant year, both a jubilee and a turning point for the church and Ukrainian monasticism. The Government of the Ukrainian SSR returned to the Ukrainian Exarchate of the ROC part of the cult buildings and the territory of the Kiev-Pechersk Lavra. Our study focuses on the process of formation and revival of monasteries and monasticism in general in Western Ukraine. The urgency of studying the activities of monasteries in Western Ukraine is due to insufficient attention of scientists to this issue. The peculiarity of studying the activities of monasteries is due to lack of material and insufficient attention of scientists to this issue. In the process of research we find the answer to the question of the destruction and destruction of monasteries and monasticism as such, the atheistic authorities of the Soviet period. The purpose of the article is to investigate the formation of Orthodox monasteries and the institute of monasticism in the UOC-KP during the period of independence of Ukraine in Western Ukraine. Monasticism as a phenomenon is increasingly attracting the attention of ordinary people. Asceticism is the driving force that helps monks perform their difficult feat. The article highlights the features of the monastery and hermitage. A comparative analysis in the interfaith dimension and in the confessional. Monasticism is the foundation of the Church. In the article the author managed to note the characteristic problems of the monasteries of the UOC-KP, this is the insufficient number of inhabitants. Insufficient fulfillment of monastic rules and monastic duties is closely related to the number of inhabitants in monasteries. Methods. The methodological basis of the study is based on the principles of objectivity and historicism using methods of analysis of historical sources, description of historical events, comparison of the development of monasteries and monasticism in general both in the interfaith dimension and in the UOC-KP in general from 1992 to 2018. Results. It was found that monasticism and monasteries began their revival with the rise of Ukraine’s independence. An interfaith analysis of the growth of monasticism and monasteries was conducted. It was revealed that the regions with the highest level of religiosity of the population and religious communities–Lviv, Zakarpattia, Ternopil, Ivano-Frankivsk became the region of active spread of monasticism. In the confessional dimension–UGCC. Among the UOC-KP, the situation in the dioceses was somewhat different. Volyn and Rivne remain the leaders, followed by Ivano-Frankivsk, Chernivtsi and Ternopil. Conclusions. Considering the peculiarities of the activity of Orthodox monasteries in Western Ukraine during the independence of Ukraine in 1992–2018, it was found that the process of formation of monasticism and their monasteries is in the process of revival and formation. The main institutional changes in the life of monasteries and monasticism of the western region of the studied period are determined.
Keywords: monasticism, UOC-KP, UAOC, UOC-MP, abbot, archimandrite, bishop, metropolitan.